2014
DOI: 10.5999/aps.2014.41.5.550
|View full text |Cite
|
Sign up to set email alerts
|

Our Experiences in Nipple Reconstruction Using the Hammond flap

Abstract: BackgroundNipple reconstruction following breast mound reconstruction is the final step in breast reconstruction. Although nipple reconstruction is a simple surgery, the psychological aspects of nipple reconstruction are thought to be important. Nipple projection is a key factor in determining patient satisfaction with the surgery. In the present study, the Hammond flap technique was introduced for nipple reconstruction.MethodsTwenty-six patients who had undergone breast reconstruction from February 2008 to Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The classical C-H flap group showed approximately 50% projection loss during the postoperative 1 year, and this rate is similar to what Hammond introduced in 2007. [ 19 , 20 ] Our modified technique reduced this projection loss rate to 38%. The projection of the reconstructed nipple of both groups at postoperative 1 year was significantly different with .002 of P value.…”
Section: Discussionmentioning
confidence: 99%
“…The classical C-H flap group showed approximately 50% projection loss during the postoperative 1 year, and this rate is similar to what Hammond introduced in 2007. [ 19 , 20 ] Our modified technique reduced this projection loss rate to 38%. The projection of the reconstructed nipple of both groups at postoperative 1 year was significantly different with .002 of P value.…”
Section: Discussionmentioning
confidence: 99%
“…Valdatta et al 12 reported that, for their 29 patients with an implant mound, the maintenance rate was 58% for the C-V flap after 12 months. For the extended latissimus dorsi flap mound, Yang et al 13 reported that the maintenance rate was 56.4% for the Hammond flap after 12 months. Compared with these data reported in the literature, we believe that our novel method is good enough and comparable with the conventional method.…”
Section: Discussionmentioning
confidence: 99%
“…Photographs were taken before, immediately and 3, 6 and 12 months after surgery. The reduction rate of each individual nipple projection was calculated using the following equation …”
Section: Methodsmentioning
confidence: 99%
“…reported that the reduction rate at 6 months was about 50%, and the reduction rate was reported to be 53%. Several other studies have analysed the long‐term preservation of nipple projection in relation to the breast mound, but the findings remain controversial. To improve surgery outcomes by avoiding these negative outcomes and donor site morbidity while maintaining long‐term nipple projection, we aimed to improve the overall nipple shape and patient satisfaction by using collagen, an alloplastic material, as the main component for reconstruction.…”
Section: Introductionmentioning
confidence: 99%